Hoop Stress Modification, Stress Hysteresis and Degradation of a REBCO Coil Due to the Screening Current Under External Magnetic Field Cycling - Takahashi, Shunji; Suetomi, Yu; Takao, Tomoaki; Yanagisawa, Yoshinori; Maeda, Hideaki; Takeda, Yasuaki; Shimoyama, Jun-ichi (IEEE transactions on applied superconductivity, 2020)
Degradation of a REBCO coil under external magnetic fields is one of the major technical problems in the field of HTS magnet technology. A possible cause of such degradation is an inhomogeneous hoop stress distribution, or hoop stress modification (both increase and decrease), induced by the screening current. In this work, we investigate such a hoop stress modification by a small coil experiment with a strain measurement and a numerical simulation. An experimental result shows a very high stress increase factor of >4.1, defined by the maximum circumferential stress over B z JR stress, and the simulated result is in qualitative agreements. The strain (stress) shows a hysteresis effect corresponding to the screening current behavior. A large hoop stress modification causes not only a hoop stress increase, but also buckling of the conductor, which induces delamination and micro-clacks of the superconducting layer. We also show the stress modification can be reduced by bonding turns with epoxy.